Transforming Public Service Delivery in Indonesia: Exploring the Potential and Challenges of the Metaverse - Hutagalung, Simon Sumanjoyo; Sulistio, Eko Budi (Jurnal Borneo Administrator, 2024)
The metaverse could transform public services. Service accessibility, efficiency, and quality can be improved through this technology. This article addresses these research questions: How does the Indonesian government use metaverse in public service? What are the primary narratives and counter-narratives around metaversebased public services in Indonesia? Which Indonesian public service using metaverse is most promising? This research evaluates and identifies public policy using the Narrative Policy Framework (NPF). Characters, setting, plot, and morals are identified for NPF analysis. According to the study, the metaverse may improve public service accessibility, efficiency, and efficacy. Infrastructure deficiency, technology allocation, and budget consideration must be considered while developing the metaverse